First Report of blaCTX–M–167, blaSHV–1, and blaTEM–1B Carrying Klebsiella pneumonia Showing High-Level Resistance to Carbapenems - Li, Shirong; Shen, Siquan; Ding, Li; Han, Renru; Guo, Yan; Yin, Dandan; Guan, Ming; Hu, Fupin (Frontiers in Microbiology, 2022)
The prevalence of carbapenem-resistant Klebsiella pneumoniae is increasing. Although carbapenemase production is the main resistance mechanism of K. pneumonia to carbapenems, there are still some reports of non-carbapenemase-producing K.pneumoniae showing high-level resistance to carbapenems. In this study, we had also isolated a carbapenemase-negative carbapenem-resistant K. pneumoniae L204 from a patient with an asymptomatic urinary tract infection. Species identification was performed using MALDI-TOF MS, and carbapenemase-encoding genes were detected using both NG-test carba-5 and whole-genome sequencing. Antimicrobial susceptibility testing was performed by the broth microdilution method according to CLSI guidance. The results of antimicrobial susceptibility testing indicated that K. pneumoniae L204 was resistant to meropenem (MIC = 16 mg/L) and imipenem (MIC = 4 mg/L), but susceptible to ceftazidime-avibactam (MIC = 8 mg/L). Through whole-genome sequencing, several resistance genes had been identified, including blaTEM–1B, blaCTX–M–167, blaSHV–1, aac(6’)-1b-cr, qnrS, aadA16, tet(A), fosA, sul1, and mph(A). The efflux pump inhibition testing showed that the efflux pump was not involved in the resistance mechanism to carbapenems. The result of the conjugation experiment indicated that the plasmid with blaCTX–M–167 and blaSHV–1 was transferrable. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) demonstrated that K. pneumoniae L204 only contained outer membrane porin OmpK35.